Development of semi-solid formulations containing Juglans regia L. leaves extracts for tropical application - Besrour, Nermine (2022)
Nowadays, cosmetic brands are urged to follow sustainable development strategies via circular economy and low carbon footprint processes. Using ingredients from agri-food waste to generate new cosmetic products and environmentally friendly solvents are one of the paths to meet those challenges [1]. In this regard, glycerol and alkanediols can be seen as alternative solvents to extract phytochemicals from plant material due to their potential application in the cosmetics area. In this work, the leaves of walnut trees (Juglans regia L.) were studied as a source of bioactive compounds. Their extracts are already used in traditional herbal medicine but can be further valorised as potential bioactive ingredients in the cosmeceutical area. The extracts were obtained using aqueous solutions of ethanol or 1,2-propanediol, and diverse bioactivity studies (antioxidant, cytotoxic, anti-inflammatory, antimicrobial, anti-tyrosinase, and photostability) were carried out. Better results were obtained with the hydroethanolic extracts in the anti-tyrosinase, antioxidant, and anti-inflammatory dimensions. In the antimicrobial assay, both extracts showed similar microbial properties. The main phytochemicals identified in both extracts were 3-O-caffeoylquinic acid, quercetin-O-pentoside, taxifolin-O-pentoside isomer, quercetin 3-O-glucoside, and 3-p-coumaroylquinic acid. After, the propanediol and hydroethanolic extracts were incorporated in a commercial base cream, aiming to design a formulation for topical application. The following parameters were studied to evaluate the stability of the final formulation: pH, colour, phenolic compounds content, and antioxidant activity. The formulation containing the hydroethanolic extract was the best to conserve the identified phenolic compounds for 30 days, at different temperature conditions (5 ºC, 20 ºC, and 40 ºC). The formulation containing the propanediol extract should be redesigned by incorporating higher amounts of extract. Both formulations presented relevant antioxidant activity and a favourable pH range of 3.8 to 4.7. These preliminary results suggest the potential application of J. regia extracts as an ingredient for incorporation into skin care products as they showed a very satisfactory chemical and physical stability at the studied time and temperature storage conditions. Nevertheless, additional studies will be performed not only to evaluate their stability over longer periods of time, but also their safety and toxicity.